Changing the Subject: Response to Düzenli, Bergeron, Amariglio, and Morton. Issue 4 (2nd October 2019) - Ruccio, David F.
Abstract : In this rejoinder, I respond to four essays on my book, Development and Globalization: A Marxian Class Analysis, by focusing on the following main themes: the contingency of theory, reading for class, subjectivity, and conjunctural analysis.